(untitled) (Research, Society and Development, 2021)
The creation of playful characters for in-service training of the Nursing team on oral anticoagulants aims to promote training strategies that contribute to overcoming gaps between knowledge and action regarding the vulnerabilities of anticoagulation therapy risks. Objective: to describe the creation and registration of playful characters to be used as facilitating instruments in the learning of the Nursing team regarding care in the administration of oral anticoagulants. Method: Methodological study with a qualitative approach, based on the development of two fictional characters named “ACO and NACO”. Results: The fictional characters, created to be agents that facilitate learning, can be recognized as a pedagogical, playful, and important tool for reflection by the Nursing team in the administration of oral anticoagulants. The hospital scenario is a complex environment, as it has very rigid, repetitive, and pre-established management structures. At the same step, the nursing team is required to seek to bridge gaps between theoretical knowledge and practice. Final Considerations: The characters suggest a way of approaching and motivating Nursing to seek more knowledge about oral anticoagulants, based on language, critical thinking and imagination.